Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1038/sj.sc.3102069
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after treatment of detrusor–sphincter dyssynergia by temporary stent

Abstract: Objectives: To evaluate follow-up treatments used after treatment of detrusor-sphincter dyssynergia (DSD) by a temporary urethral sphincter stent. Materials and methods: Between February 1994 and June 2003, 147 men with a mean age of 41.3714.4 years were treated by temporary urethral stent inserted across the external sphincter for DSD. The underlying neurologic disease was quadriplegia in 85 cases, multiple sclerosis in 24 cases and paraplegia in 21 cases. A Nissenkorn (Bard) stent was used in 130 cases and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 20 publications
(26 reference statements)
0
13
0
1
Order By: Relevance
“…Two types of BND have been described, which may differ between tetraplegia and paraplegia: one is secondary to AD and the other is associated with loss of supraspinal inhibitory control on the vesico-sympathetic reflex. 19 Vesicoureteral reflux is known to improve after surgical sphincterotomy or urethral stenting, 3,9 or urethral injection. 8,13 Our study confirms this, as reflux was found to have disappeared in all patients who underwent repeat cystourethrograms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two types of BND have been described, which may differ between tetraplegia and paraplegia: one is secondary to AD and the other is associated with loss of supraspinal inhibitory control on the vesico-sympathetic reflex. 19 Vesicoureteral reflux is known to improve after surgical sphincterotomy or urethral stenting, 3,9 or urethral injection. 8,13 Our study confirms this, as reflux was found to have disappeared in all patients who underwent repeat cystourethrograms.…”
Section: Discussionmentioning
confidence: 99%
“…Sphincteric stenting is another option with a satisfactory success rate of 75% at 3 months; however, this technique is also associated with short-and long-term complications. 9 The reasons for the failure of botulinum toxin injections are not fully understood: detrusor underactivity, 1 bladder neck dyssynergia (BND), 1,7 type of DSD and the dose or dilution of the toxin 10 have been suggested to affect effectiveness. However, few studies have been carried out, and the samples included are generally small.…”
Section: Introductionmentioning
confidence: 99%
“…If a temporary stent ensured effective bladder emptying, a permanent stent was used. 23 Until today, however, no perfect permanent stent exists, because in longterm follow up, permanent stents caused significant problems in a significant proportion of patients. Urothelial ingrowth can be a long-term problem, leading to recurrent endoscopic resections.…”
Section: Discussionmentioning
confidence: 99%
“…Seules demeurent les endoprothèses à spire jointive temporaires Memocath ® (Bard) et Diabolo ® (Coloplast-Porges). Ces prothèses peuvent être utiles à la sélection des patients candidats à une sphinctérotomie [22,23]. Il faut discuter chez les répondeurs le changement itératif d'endoprothèse temporaire ou la sphinctérotomie endoscopique classique.…”
Section: Discussionunclassified